2015
DOI: 10.1111/cns.12469
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 ligand Poly IC Attenuates Reactive Astrogliosis and Improves Recovery of Rats after Focal Cerebral Ischemia

Abstract: SUMMARY Aims Brain ischemia activates astrocytes in a process known as astrogliosis. Although this process has beneficial effects, excessive astrogliosis can impair neuronal recovery. Polyinosinic–polycytidylic acid (Poly IC) has shown neuroprotection against cerebral ischemia–reperfusion injury, but whether it regulates reactive astrogliosis and glial scar formation is not clear. Methods We exposed cultured astrocytes to oxygen–glucose deprivation/reoxygenation (OGD/R) and used a rat middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 50 publications
6
49
0
1
Order By: Relevance
“…Beneficial effects were also observed in rats, using a similar approach [88]. These data support the potential for TLR3 agonists in brain I/R injury, such as stroke.…”
Section: Therapeutic Implicationssupporting
confidence: 71%
See 3 more Smart Citations
“…Beneficial effects were also observed in rats, using a similar approach [88]. These data support the potential for TLR3 agonists in brain I/R injury, such as stroke.…”
Section: Therapeutic Implicationssupporting
confidence: 71%
“…As indicated earlier (see Section 2.3), TLR3 has previously been implicated in mediating loss of BBB integrity and contributing to neuropathology in a mouse model of WNV infection [30]. Nonetheless, recent studies have reported protective effects of poly(IC) treatment in brain I/R injury models [87][88][89]. This was linked to the capacity of TLR3 signalling in human astrocytes to drive expression of anti-inflammatory cytokines, such as Ifn-, which act as neuroprotective factors [87,88].…”
Section: I/r Injury In the Brainmentioning
confidence: 87%
See 2 more Smart Citations
“…29 In addition, poly I:C is a potential therapeutic agent useful for attenuating neuronal damage and promoting recovery after brain ischemia. 30 However, stability issues limit the clinical application of poly rI and poly I:C that undergo facile enzymatic degradation. Hence is the need for technological approaches aimed to improve the delivery and consequent efficacy of these RNAs.…”
Section: Sem Analysismentioning
confidence: 99%